Complications after fibula intramedullary nail fixation of pilon versus ankle fractures - Faber, Rachel M. (J Clin Orthop Trauma, 2021)
BACKGROUND: Intramedullary nail (IMN) fixation of the fibula in malleolar ankle fractures has been shown to result in less wound complications then plate fixation. Therefore, IMN fibula fixation may also be associated with lower rates of wound complications when used for higher-risk pilon fractures. The purpose of this study was to compare complications of fibula IMN fixation in pilon versus malleolar ankle fractures. METHODS: A retrospective cohort comparison was performed at an urban level one trauma center involving fibula fractures in 47 patients with AO/Orthopaedic Trauma Association (OTA) type 43 fractures and 48 patients with AO/OTA type 44 fractures being treated with fibula IMN fixation. Complications, fibula-specific complications, revision surgeries, and implant removals were reviewed. RESULTS: There was no detectable difference in complications (27% vs. 23%, 95% confidence interval of the odds ratio (CIOR) 0.5 to 3.2), fibular-specific complications (6% vs. 10%, CIOR 0.1 to 3.5), revision surgeries (4% vs. 4%, CIOR 0.1 to 7.5), or symptomatic fibula implant removals (13% vs. 21%, CIOR 0.1 to 1.6) between pilon and ankle fracture groups, respectively. There was one (2%) fibular nonunion and one wound complication (2%) in each of the fracture groups. CONCLUSION: Fibula IMN fixation of pilon versus ankle fractures resulted in a similar number of complications. Comparative studies of fibula IMN and plate fixation are necessary to determine if the benefits of fibula IMN in ankle fractures extends to pilon fractures. LEVEL OF EVIDENCE: Level III, retrospective cohort.